Polymer–Lipid Nanoparticles for Systemic Delivery of mRNA to the Lungs. Issue 44 (30th September 2016) - Kaczmarek, James C.; Patel, Asha K.; Kauffman, Kevin J.; Fenton, Owen S.; Webber, Matthew J.; Heartlein, Michael W.; DeRosa, Frank; Anderson, Daniel G.
Abstract: Therapeutic nucleic acids hold great promise for the treatment of disease but require vectors for safe and effective delivery. Synthetic nanoparticle vectors composed of poly(β‐amino esters) (PBAEs) and nucleic acids have previously demonstrated potential utility for local delivery applications. To expand this potential utility to include systemic delivery of mRNA, hybrid polymer–lipid nanoformulations for systemic delivery to the lungs were developed. Through coformulation of PBAEs with lipid–polyethylene glycol (PEG), mRNA formulations were developed with increased serum stability and increased in vitro potency. The formulations were capable of functional delivery of mRNA to the lungs after intravenous administration in mice. To our knowledge, this is the first report of the systemic administration of mRNA for delivery to the lungs using degradable polymer–lipid nanoparticles. Abstract : mRNA‐loaded nanoparticles were synthesized using degradable poly(β‐amino ester) terpolymers formulated with a PEG‐lipid. The PEG‐lipid imparted serum stability to the nanoparticles, which resulted in successful mRNA delivery to the lungs after systemic nanoparticle administration in mice.